Chemical and Biological Evidence of the Efficacy of Shengxian Decoction for Treating Human Lung Adenocarcinoma - Li, Kejuan; You, Fengming; Zhang, Qin; Yuan, Ruijiao; Yuan, Qianghua; Fu, Xi; Ren, Yifeng; Wang, Qian; Li, Xiaohong; Zhang, Zhenya; Shichiri, Mototada; Yu, Yue (Frontiers in Oncology, 2022)
Shengxian Decoction (SXT) is a traditional Chinese medicine prescription comprising several anti-cancer medicinal herbs. However, the anti-cancer effect of SXT has rarely been reported. Herein, we explored the therapeutic potential of SXT for the treatment of lung adenocarcinoma (LUAD). High-performance liquid chromatography analysis of crude SXT extract revealed the abundance of mangiferin, an established anti-cancer compound. The serum pharmacological evaluation revealed that serum SXT suppressed A549 lung cancer cell proliferation in vitro. The tumor-inhibitory activity of SXT was confirmed in vivo via tumor formation assays in nude mice. We applied biochemical, histopathological and imaging approaches to investigate the cellular targets of SXT. The results indicated that the treatment with SXT induced tumor necrosis, and downregulated hypoxia-inducible factor 1 alpha in the serum. In vivo biosafety assessment of SXT revealed low levels of toxicity in mouse models. Our study provides the first scientific evidence that SXT effectively represses cancer cell growth and, thus, may serve as a safe anti-cancer agent for LUAD treatment.